2009
DOI: 10.1177/1043659609340803
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and Advance Care Planning in a Culturally Diverse Society

Abstract: Emerging international research suggests that in multicultural countries, such as Australia and the United States, there are significant disparities in end-of-life care planning and decision making by people of minority ethnic backgrounds compared with members of mainstream English-speaking background populations. Despite a growing interest in the profound influence of culture and ethnicity on patient choices in end-of-life care, and the limited uptake of advance care plans and advance directives by ethnic min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
140
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 46 publications
3
140
0
Order By: Relevance
“…As a result, the applicability of our results to more diverse populations who do not speak English or French as a first language and who may have different values related to end-oflife care 22,23 remains uncertain. Although we were able to enroll most of the eligible patients and family members (62% and 74%, respectively), thus minimizing selection bias, non-consenting patients or family members may have had different perspectives on what is important during end-of-life communication and decision-making.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As a result, the applicability of our results to more diverse populations who do not speak English or French as a first language and who may have different values related to end-oflife care 22,23 remains uncertain. Although we were able to enroll most of the eligible patients and family members (62% and 74%, respectively), thus minimizing selection bias, non-consenting patients or family members may have had different perspectives on what is important during end-of-life communication and decision-making.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The diversity of the Australian population, 25 cultural influences in ACP 11 and direction towards culturally appropriate ACP 2 provide strong rationale for the development of such resources. Resources should support health professionals and consumers in the preparation and participation of culturally appropriate ACP conversations while ensuring respect for people and avoidance of generalisations, as consistent with the identified existing combined resources.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of value assumptions between Western and minority cultural worldviews highlights differences in autonomy, decision-making processes, family inclusivity, control over dying and disclosure that affect ACP. 11 Since the initiation of ACP, resources have evolved, with many available on the Internet. 12,[15][16][17] A recent review identified the availability of Australian online ACD templates, but did not examine specific cultural and religious information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge can be used for educating nurses who are future primary care providers. It is a professional responsibility, especially since many nurses with a graduate degree may work in oncology settings [1,2].…”
Section: Introductionmentioning
confidence: 99%